PENGGAMBARAN CITRA SEHAT DALAM IKLAN SABUN BATANGAN LIFEBUOY BAHASA INGGRIS (ANALISIS MIKROSTRUKTURAL DAN MAKROSTRUKTURAL) - Elsan Arvian (Ennichi, 2020)
The problems discussed in this research are (1) what are the microstructural aspects that build discourse on Lifebuoy bar soap advertisements? (2) What are the macrostructural aspects that build discourses on Lifebuoy bar soap advertisements? This type of research is a descriptive qualitative research. The data source used is the written data source for Lifebuoy bar soap advertisements which are downloaded from the official website of lifebuoy.co.id. The data in this study are in the form of words, phrases in lines on Lifebuoy bar soap advertisements that contain discourses on microstructural and macrostructural aspects. Data classification in this study was carried out by sorting and selecting data according to the research objectives of the discourse on microstructural and macrostructural aspects. The method of providing data in this study is the observation method. This method will be realized through advanced technique I: Speaking Free Talking Technique or SBLC technique and advanced technique II: note taking technique. This technique is carried out by taking data related to the problem being studied, namely the microstructural and macrostructural discourse. The methods and data analysis techniques used are the split method and referential equivalent method. Agih method is used to analyze microstructural aspects, namely grammatical and lexical aspects. The equivalent method is used to analyze the macrostructural aspects, namely contextual. The data presentation method used is the informal presentation method. The results of the discussion and data analysis show that: (1) The microstructural aspect of the data source is found markers of grammatical and lexical aspects. There were 39 reference markers, 0 substitution markers, 3 ellipsis markers, 32 conjunction markers, the most common markers were reference markers, (2) Macrostructural aspect implies that the dominance of reference markers is likely to indicate lifebuoy bar soap is the pioneer of health soap.